Musichology and Structural Analysis of Music. Reflexions and Pontis of Encounter (2021)
This paper proposed here corresponds to the results of the development of the first phase of the research project "Fonoteca de la Banda Sinfónica de Vientos de Boyacá". In which, the need to restore the sound archive of the assembly is raised based on advances made in the preservation of existing documentary material. Therefore, to address a search and systematization of sound information, it was necessary, initially, to detail the importance of musicology and musical analysis, as tools that contribute to the preservation of the cultural legacy. In this way, it seeks to present a theoretical approach to the concept of musicology and how it has contributed, as a discipline of musical theory, to the historical and contextual study of society and culture, through the explanation and analysis of musical compositions arising in the different moments of human history. As a working element of musicology, musical analysis is presented, an exercise that covers aspects such as origin, history, and political-social environment, in a global framework of the work, as well as how the author or composer manages to condense these episodes into a single musical piece based on subjective and objective aspects. The instrumental interpretation of works varies according to whether they are arranged for soloists or groups, about to with concerning the elements of a musicological and philosophical type that integrate them, and that from the point of view of musical analysis would have to be known to the interpreter. This phase of research is entirely hermeneutical theoretical since the whole approach is subject to the concepts of musical analysis and musicology, and the experiences that researchers have carried out in this field.